Composite two-Higgs doublet model from dilaton effective field theory - Maurizio Piai (Nuclear Physics B, 2022)
We construct a composite two-Higgs-doublet model (2HDM) within the context of dilaton effective field 24 theory. This EFT describes the particle spectrum observed in lattice simulations of a near-conformal SU(3) 25 gauge field theory. A second Higgs doublet is naturally accommodated within the EFT, used previously 26 to construct a one-Higgs-doublet model. We explore the interplay of phenomenological and EFT require- 27 ments, supplemented by information from numerical lattice studies of the SU(3) gauge theory with eight 28 fundamental (Dirac) fermions. We build a viable model with moderate parameter tuning. In the relevant 29 portion of parameter space, we match the model to a conventional general description of 2HDMs, and com- 30 ment on the role of custodial symmetry (breaking) in the scalar potential. Contributions to the precision 31 electroweak parameter T provide a possible explanation for the recent measurement of the W-boson mass 32 by CDF II.